Hsf-1 affects podocyte markers NPHS1, NPHS2 and WT1 in a transgenic mouse model of TTRVal30Met-related amyloidosis. (5th July 2013) - Petrakis, Ioannis; Mavroeidi, Vasiliki; Stylianou, Kostas; Andronikidi, Eva; Lioudaki, Eirini; Perakis, Kostas; Stratigis, Spyridon; Vardaki, Eleftheria; Zafeiri, Maria; Giannakakis, Kostantinos; Plaitakis, Andreas; Amoiridis, George; et al.
Abstract: Introduction : Familial amyloid polyneuropathy is characterized by transthyretin (TTR) deposition in various tissues, including the kidneys. While deposition induces organ dysfunction, renal involvement in TTR-related amyloidosis could manifest from proteinuria to end-stage kidney failure. As proteinuria is considered result of glomerular filtration barrier injury we investigated whether TTR deposition affects either glomerular basement membrane (GBM) or podocytes. Materials and methods : Immunohistochemistry, immunoblot and gene expression studies for nephrin, podocin and WT1 were run on renal tissue from human-TTRV30M transgenic mice hemizygous or homozygous for heat shock factor one (Hsf-1). Transmission electron microscopy was used for evaluation of podocyte foot process width (PFW) and GBM thickness in Hsf-1 hemizygous mice with or without TTRV30M or amyloid deposition. Results : Glomeruli of hsf-1 hemizygous transgenic mice showed lower nephrin and podocin protein levels but an increased podocyte number when compared to Hsf-1 homozygous transgenic mice. Nephrin, podocin and WT1 gene expression levels were unaffected by the Hsf-1 carrier status. TTRV30M deposition was associated with increased PFW and GBM thickness. Conclusions : Under the effect of Hsf-1 hemizygosity, TTRV30M deposition has deleterious effects on GBM thickness, PFW and slit diaphragm composition, without affecting nephrin and podocin gene expression.